2017
DOI: 10.1038/ijos.2017.46
|View full text |Cite
|
Sign up to set email alerts
|

Quaternary ammonium-induced multidrug tolerant Streptococcus mutans persisters elevate cariogenic virulence in vitro

Abstract: Dental caries are the most prevalent chronic infections in the oral cavity, and Streptococcus mutans acts as the main cariogenic bacterial species. Antibacterial quaternary ammonium compounds (QAs) have been developed to preveFnt or treat dental caries. However, there is no report on the tolerance of S. mutans to QAs. In this study, we investigated the development of S. mutans persistence induced by a novel dental caries defensive agent, dimethylaminododecyl methacrylate (DMADDM), for the first time. Typical b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 59 publications
0
19
0
Order By: Relevance
“…The water-soluble glucans, as a rich carbon source, may play an important role depending on the state of persister biofilms. Our previous study proved that in the dormant state, the addition of glucose significantly reduced the number of persister cells (Jiang et al, 2017). It indicated that the addition of carbon sources can reverse the dormancy of the bacteria to resuscitation.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…The water-soluble glucans, as a rich carbon source, may play an important role depending on the state of persister biofilms. Our previous study proved that in the dormant state, the addition of glucose significantly reduced the number of persister cells (Jiang et al, 2017). It indicated that the addition of carbon sources can reverse the dormancy of the bacteria to resuscitation.…”
Section: Discussionmentioning
confidence: 82%
“…In our previous work, we have monitored the expression of several key glycolysis-and citrate cycle-related genes in S. mutans persister cells, including adhE, ldh, and pdhA/B/C/D. The expression levels of these genes were all significantly downregulated in persistent cells compared to the control group, suggesting the low metabolic level of S. mutans persisters (Jiang et al, 2017). Contrarily, in this study we observed the S. mutans persisters were metabolically active in "lag time" when they reverse from dormancy to regrowth in terms of quorum-sensing and two component system VicRK pathways.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the quaternary amines dimethylaminododecyl methacrylate (DMADDM) and benzalkonium chloride (BZK) induced development of drug resistance in a biofilm model of S. gordonii . Likewise, exposure to the QAC DMAHDM induced drug tolerance in an S. mutans biofilm model …”
Section: Antimicrobial Composites and Adhesivesmentioning
confidence: 99%